O’NEIL’S SURVIVAL TACTICS IN GAINING EQUALITY IN DAVID TWOHY’S G. I JANE - Prita Jonathan; Liliek Soelistyo (Institute of Research and Community Outreach - Petra Christian University, 2013)
This article tries to reveal about O’Neil’s survival tactics in gaining gender equality in the Military. By using the tactics such as contradictory tactic, overcompensation and demonstrating proficiency at the required tasks, the analysis shows the ways she overcomes the difficulties in the Military training as a woman. In adapting with all the requirements, O’Neil wants to prove that she is as capable as any other male candidate there. Moreover, she also wants to overcome her differences from men so that they can acknowledge her as a part of them. In conclusion, O’Neil can show her survival tactics in gaining equality because she is willing to overcome the difficulties in the Military.